Gender and Crime: Contemporary Theoretical Perspectives - Browning, Sandra L. (Advances in Criminological Theory Series, 2024)
This volume in the Advances in Criminological Theory series takes stock of contemporary perspectives on gender and crime. The book will be of great interest to a wide range of criminologists and is an ideal choice for use in graduate seminars and upper-level undergraduate courses.